Research progress on correlations between trace element levels and epilepsy - Liu, Wanyu; Xu, Jingqing; Zhang, Linhai; Li, Fangjing; Zhang, Lijia; Tai, Zhenzhen; Yang, Juan; Zhang, Haiqing; Tuo, Jinmei; Yu, Changyin; Xu, Zucai (Frontiers in Cell and Developmental Biology, 2023)
Research investigating the correlation between human trace element levels and disease alterations is growing. Epilepsy, a common nervous system disease, has also been found to be closely related to abnormal levels of trace elements. Studies continue to explore mechanisms of various trace elements involved in epileptic seizures through experimental animal models of epilepsy. Thus, we reviewed the research progress on the correlation between trace element levels and epilepsy in recent years and found that the trace elements most closely related to epilepsy are mainly metal ions such as selenium, iron, copper, zinc, and manganese. These results indicate that the changes in some trace elements are closely related to the increase in epilepsy susceptibility. In addition, after treatment with drugs and a ketogenic diet, the concentration of trace elements in the serum of patients with epilepsy changes. In other words, the abnormality of trace element concentrations is of great significance in the occurrence and development of epilepsy. This article is a literature update on the potential role of trace element imbalance in the development of epilepsy, providing new references for the subsequent prevention and treatment of epilepsy.